1996
DOI: 10.1002/eji.1830260622
|View full text |Cite
|
Sign up to set email alerts
|

Dispensability of Jak1 tyrosine kinase for interleukin‐2‐induced cell growth signaling in a human T cell line

Abstract: The tyrosine kinases Jak1 and Jak3 are known to be associated with the beta and gamma chains of interleukin-2 receptor (IL-2R). They are activated by stimulation with IL-2, IL-4, IL-7, IL-9, or IL-15, receptors of which share the gamma chain of the IL-2R. We have obtained direct evidence of Jak1 association with the alpha chains of receptors for IL-4, IL-7 and IL-9 and with the beta chain of IL-2R, which is also common to the IL-15R. Furthermore, we have prepared mutant IL-2R beta chains with a mutation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
2
25
0
2
Order By: Relevance
“…Analysis of IL-2 signaling in B cell lines lacking JAK3 has demonstrated that IL-2-induced phosphorylation of IL-2␤, JAK1, and STAT5 all require the presence of JAK3 (19). In contrast, it has been suggested that JAK1 activation is not required for activation of JAK3 and STAT5 in the human T cell line (40). These findings strongly suggest that phosphorylation of JAK3 is important in IL-2 signaling, and the importance of JAK1 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of IL-2 signaling in B cell lines lacking JAK3 has demonstrated that IL-2-induced phosphorylation of IL-2␤, JAK1, and STAT5 all require the presence of JAK3 (19). In contrast, it has been suggested that JAK1 activation is not required for activation of JAK3 and STAT5 in the human T cell line (40). These findings strongly suggest that phosphorylation of JAK3 is important in IL-2 signaling, and the importance of JAK1 remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytically active Jak3 is required for IL-2-driven tyrosine phosphorylation of Jak1 and Stat5a/b (12,23,24,40,41). Moreover, since Stat5a/b gene-deficient mice are unable to proliferate in response to IL-2, we examined whether AG-490 inhibits IL-2-induced activation of Stat5a/b via Jak3.…”
Section: Ag-490 Inhibits Jak3 Activation and Stat5a/b Tyrosine And Sementioning
confidence: 99%
“…To evaluate whether the parallel decline in proliferation and decreased phosphorylation of STAT5 reflected a change in binding to specific promoter regions, we performed gel-shift analysis using a bovine ␤-casein promoter sequence encoding a STAT-binding consensus motif (38). Upon phosphorylation, STAT proteins are FIGURE 7.…”
Section: Dna-binding Activity Of Stat5 Is Reduced In Anergized T Cellmentioning
confidence: 99%